Inconstitucionalidade da proibição do Uber à luz da defesa da concorrência - Lima, Jonas Guedes de (2019)
The purpose of this thesis was to demonstrate, through economic liberalism and free competition, the insertion of the Uber platform into a service category previously performed only by taxi drivers, individual passenger transportation. Technological resources are advanced in order to make life easier, today there are a lot of products and services offered with just the touch of the fingers just have a smartphone connected to the internet. However, such facilities are part of the disruptive technology that breaks down barriers and modifies the way of societies consume. The Uber platforms arrived in Brazil in 2014, with the purpose of offering paid rides, and entered at the market revolutionizing the way of people requested and use individual transportation, causing problems in a market exploited only by taxi drivers. It was not possible to claim unconstitutionality in the service, since the Federal Constitution guarantees to the market the free competition.